ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM DENGAN MENGGUNAKAN MODEL INDEKS TUNGGAL (Studi Pada Saham LQ-45 di Bursa Efek Indonesia Periode Agustus 2009-Juli 2012) - Susanti Susanti; Syahyunan Syahyunan (Universitas Sumatera Utara, 2013)
ABSTRACT The purposes of this study are to analyze the stocks that is formed in the optimal portfolio of stocks in the LQ-45 index and the proportion, as well as to analyze the level of expected return and risk of the portfolio formed. The type of this study is descriptive study. Secondary data in this study is the monthly stocks prices data of listed companies in the LQ-45 index, The monthly Composite Stock Price Index (IHSG), and the monthly interest rates of Bank Indonesia. The data was processed using Microsoft Excel 2007. The research samples are the companies’s stock listed consecutively in 6 (six) periods LQ-45 such as the period August 2009-January 2010, February 2010-July 2010, August 2010-January 2011, February 2011-July 2011, August 2011-January 2012, and February 2012-July 2012, as many as 27 (twenty seven) companies. The results of the study are 6 (six) shares of companies that meet the criterias for the determining optimal portfolio shares, PT Unilever Indonesia Tbk. (UNVR) with the 36,473% proportion of funds, PT Gudang Garam Tbk. (GGRM) with the 16,12% proportion of funds, PT Kalbe Farma Tbk. (KLBF) with the 21,046% proportion of funds, PT Jasa Marga (Persero) Tbk. (JSMR) with the 25,736% proportion of funds, PT Indocement Tunggal Prakarsa Tbk. (INTP) with the 0,0412% proportion of funds, and PT Semen Indonesia (Persero) Tbk. (SMGR) with the 0,212% proportion of funds. Optimal portfolio has formed promised 3,737% the expected return with 4,833% the rate of risk. Keywords: Optimal Portfolio, Single Index Model, LQ-45 Index